Causation and gravitation in George Cheyne's Newtonian natural philosophy. (February 2021) - Connolly, Patrick J.
Abstract: This paper analyzes the metaphysical system developed in Cheyne's Philosophical Principles of Religion . Cheyne was an early proponent of Newtonianism and tackled several philosophical questions raised by Newton's work. The most pressing of these concerned the causal origin of gravitational attraction. Cheyne rejected the occasionalist explanations offered by several of his contemporaries in favor of a model on which God delegated special causal powers to bodies. Additionally, he developed an innovative approach to divine conservation. This allowed him to argue that Newton's findings provided evidence for God's existence and providence without the need for continuous divine intervention in the universe. Highlights: Refocuses attention from Cheyne's medical work onto his metaphysical views. Explores Cheyne's claims about the nature and cause of gravitational attraction. Highlights efforts to use scientific findings to buttress religious belief. Showcases Cheyne's innovative recasting of the doctrine of divine conservation. Emphasizes Cheyne's substantial contribution to the construction of "Newtonianism".